Religious conversion among high security hospital patients: a qualitative analysis of patients accounts and experiences on changing faith - Thomas, Azania; Völlm, Birgit; Winder, Belinda; Abdelrazek, Tarek (Taylor & Francis, 2016)
Research has shown the importance of religion in recovery from mental illness. Previous studies have investigated why individuals change faith during custody in prison, but there has been no of religious conversion among patients detained in a UK secure research to date on religious conversion in forensic-psychiatric hospitals. The aim of this study was to understand the experience hospital. Thirteen patients who had converted their religion were interviewed and the resultant data were analysed using thematic analysis. Three superordinate themes (“reasons for changing faith”, “benefits of having a new faith” and “difficulties with practising a faith”) , incorporating eight subordinate themes, emerged. Understanding patients’ reasons for religious conversion is important for the treatment and support not merely of these individuals, but more broadly with patients in forensic-psychiatric care.